ANALISIS IMPLEMENTASI SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA PERUSAHAAN MEBEL (Studi Pada Pada Himpunan Industri Mebel Dan Kerajinan Indonesia, Komisi Daerah Jepara Raya) - Miswan Ansori (Akademi Akuntansi YKPN Yogyakarta, 2017)
Furniture industry is an industrial sector that survive from economic crisis in Indonesia, because every year the demand for furniture products always increases with increasing population growth. Furniture industry in Jepara has become a regional identity for Jepara then it needs to be preserved. Supply Chain Management is a supply life cycle concept that integrates and coordinates the overall process of the furniture company in preparing and delivering products or services ranging from suppliers of raw materials to the company and then sent to consumers. With the existence of various stakeholder relations, relationships and the effects of information sharing, long-term relationships and integration process occurring between several parties related to the supply life cycle from and to the company are important variables in assessing Supply Chain Management's performance implemented by furniture companies in Jepara. Keywords: Supply Chain Management, Information Sharing, Long Term Relationship, Integration Process